Mediating Pathways to Productivity: How Job Satisfaction Bridges Leadership and Commitment to Performance in Indonesia - Firmansyah, Akbar Maulana (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
Employee performance in resource-constrained environments hinges on leadership and organizational commitment, yet the mediating mechanisms remain underexplored. This study examines how supportive leadership and organizational commitment influence job performance directly and through job satisfaction among formal sector employees in East Java, Indonesia, a region grappling with high turnover intentions, “quiet quitting,” and lagging productivity. Drawing on Path-Goal Theory and Meyer and Allen’s three-component model of commitment, we hypothesize dual pathways linking leadership and commitment to performance, mediated by satisfaction. Data from 381 employees across 26 districts were analyzed using PLS-SEM. Results confirm organizational commitment (β = 0.296, p < 0.001) and supportive leadership (β = 0.349, p < 0.001) directly enhance job performance, while job satisfaction mediates these relationships (indirect effects: 0.200 and 0.095, p < 0.01). Commitment also strongly predicts satisfaction (β = 0.623, p < 0.001), as does leadership (β = 0.297, p < 0.001), with satisfaction itself driving performance (β = 0.321, p < 0.001). The model explains 86.1% of performance variance, underscoring satisfaction’s pivotal role in translating socio-emotional resources into productivity. Practical implications advocate for leadership development programs that emphasize empathy and transparency, paired with commitment-building initiatives to foster emotional attachment. These strategies offer cost-effective solutions for policymakers and organizations aiming to mitigate turnover, stimulate discretionary effort, and enhance economic resilience in emerging markets. By bridging affective and behavioral dimensions, this research advances HRM theory while providing actionable insights for sustaining workforce engagement in contexts marked by macroeconomic precarity.